Colorado water, January/February 2013 - Middleton, Lindsey A., editor; Colorado Water Institute, publisher (Colorado State University. Libraries, 2013)
Newsletter of the Water Center of Colorado State University. Theme: Water education.
The newsletter is devoted to enhancing communication between Colorado water users and managers and faculty at the state's research universities.
Keywords: Water resources development -- Colorado; Water use -- Colorado; Water-supply -- Colorado; Water-supply -- Management -- Colorado